1991
DOI: 10.3109/02699059109008107
|View full text |Cite
|
Sign up to set email alerts
|

The effects of head injury in children on neuropsychological and behavioural functioning

Abstract: In a prospective study 76 children were divided into three groups on the basis of severity of head injury as defined by the Glasgow Coma Scale and duration of increased intracranial pressure. The children were administered a neuropsychological test battery and behavioural ratings were made by parents and teachers at three intervals: time of hospital discharge and 3 and 9 months post-initial testing. There were cognitive deficits related to severity of injury with the greatest difference in abilities observed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
81
0
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 29 publications
(22 reference statements)
10
81
0
2
Order By: Relevance
“…For example, O'Leary et al (1983) found that school-aged children and adolescents with early onset epileptic seizures (before age 5) performed more poorly on both Parts A and B compared to those children with late onset seizures. Knights et al (1991) reported that children with severe traumatic brain injuries took more time to complete Parts A and B of the TMT than children with mild and moderate head injuries. However, Ewing-Cobbs et al (1998) found that TMT performance differences were due to age, but not due to the severity of the injury, in a sample of 91 children who had incurred traumatic brain injuries.…”
Section: Introductionmentioning
confidence: 99%
“…For example, O'Leary et al (1983) found that school-aged children and adolescents with early onset epileptic seizures (before age 5) performed more poorly on both Parts A and B compared to those children with late onset seizures. Knights et al (1991) reported that children with severe traumatic brain injuries took more time to complete Parts A and B of the TMT than children with mild and moderate head injuries. However, Ewing-Cobbs et al (1998) found that TMT performance differences were due to age, but not due to the severity of the injury, in a sample of 91 children who had incurred traumatic brain injuries.…”
Section: Introductionmentioning
confidence: 99%
“…These rates of clinically significant change were somewhat lower than anticipated, but may be attributable to the use of a lower cutoff score. This finding also is consistent with literature that suggests low sensitivity to the behavioral sequelae of pediatric TBI (Kinsella et al, 1995;Knights et al, 1991). In fact, two studies found that structured interviews identified more post-TBI behavior problems than parent ratings (Bloom et al, 2001;Green, Foster, Morris, Muir, & Morris, 1998).…”
Section: Summary Of the Current Worksupporting
confidence: 81%
“…Clearly, global insults in brain function impair one's ability to perform in many domains of cognitive testing, and this manner of impairment can be reversed with clinical improvement in general brain function (Knights et al, 1991;Mandleberg and Brooks, 1975;Mayes et al, 1989;White et al, 1986). This raises the question of whether the improvements we observed represent a true cognitive enhancement per se or simply restoration of more effective utilization of cognitive resources that pre-existed the symptomatic state of psychosis and that were unavailable or dysfunctional during the more clinically disturbed state.…”
Section: Discussionmentioning
confidence: 61%